EPISTEMOLOGI BAYANI, BURHANI, IRFANI DALAM INTEGRASI KEILMUAN - Musalam; Akhyak; Ngainun Naim (As-Sulthan Journal of Education, 2026)
The development of modern scientific knowledge demands an educational paradigm capable of integrating Islamic values with rational and empirical approaches. Since the classical period, the Islamic intellectual tradition has offered three epistemological frameworks—bayani, burhani, and irfani—each possessing distinct characteristics in the process of knowledge production. This study aims to analyze the relationship, contributions, and implementation of these three epistemologies within the integration of knowledge in Islamic education. The method employed is a library research approach by examining books, journal articles, conference proceedings, and academic documents through the stages of literature inventory, classification, content analysis, and synthesis. The findings indicate that the bayani epistemology functions as a normative foundation for understanding revealed texts through linguistic principles and ushul fiqh methodologies. Burhani serves as a rational-empirical framework emphasizing demonstrative logic and verification of reality, making it relevant for strengthening scientific methods. Irfani complements both by providing a spiritual, ethical, and intuitive dimension as the basis for character formation in learners. The implementation of these three epistemologies in education can be realized through the integration of text-based learning (bayani), scientific research and observation (burhani), as well as moral and spiritual development (irfani). The synergy among them forms a holistic model of Islamic education that is adaptive to contemporary developments while remaining rooted in Islamic values. This study affirms that the epistemological integration of bayani, burhani, and irfani serves as an essential foundation for constructing a comprehensive Islamic scientific paradigm relevant to the needs of the modern era.